External Assessment of the Anti-N-Methyl-D-Aspartate Receptor Encephalitis One-Year Functional Status Score in Chinese Pediatric Patients - Luo, Hanyu; Li, Yuhang; Zheng, Yaxin; Zhou, Lvli; Yang, Jiaxin; Fang, Zhixu; Jiang, Yan; Wang, Juan; Yao, Zhengxiong; Chen, Min; Jiang, Li (Frontiers in Immunology, 2022)
Objective: to assess the performance of the Anti-N-Methyl-D-Aspartate Receptor encephalitis (NMDAR) One-Year Functional Status (NEOS) score in predicting one year functional outcome in Chinese children with anti-NMDAR encephalitis. Methods: children with anti-NMDAR encephalitis at the Children’s Hospital of Chongqing Medical University were retrospectively enrolled from January 2014 to December 2020. Patients were categorized into two groups based on the modified Rankin Scale (mRS) at one year follow-up. Discrimination of the NEOS score was assessed by the area under curve (AUC) of the receiver operating characteristic curve. Calibration of the NEOS score was assessed via comparing predicted probabilities with observed probabilities using a calibration curve and the Hosmer-Lemeshow test. Clinical practicability of the NEOS score was evaluated by performing a decision curve analysis. Results: a total of 189 children (112 females and 77 males) with anti-NMDAR encephalitis and a median age of 7.7 years were enrolled. Of those, 162 (85.7%) had a good outcome at 1 year (mRS ≤ 2) and the remaining 27 (14.3%) had a poor outcome (mRS > 2). Patients with a higher NEOS score had a significantly higher mRS at one year follow-up [Spearman r = 0.3817, 95% confidence interval (CI): 0.2487-0.5005, P < 0.001]. The AUC of the NEOS score was 0.863 (95% CI: 0.795-0.930, P < 0.001). The observed probability and predicted probability showed moderate consistency in the calibration curve and the Hosmer-Lemeshow test (P = 0.464). The decision curve analysis showed that using the NEOS score to predict one-year outcome could provide additional net benefit during clinical practice. Conclusions: the NEOS score is a potentially reliable model to predict the one year functional outcome in Chinese children with anti-NMDAR encephalitis.